Performance of commercial poultry offal meal as fishmeal replacement in the diet of juvenile Malaysian mahseer, Tor tambroides - Ismail, Saufinas; Kamarudin, Mohd Salleh; Fard, Ehsan Ramezani (Academic Journals, 2013)
Mahseer is one of the most expensive freshwater fish in Malaysia and has a good potential for freshwater aquaculture industry. This study was conducted to evaluate the suitability of Poultry Offal Meal (POM) as Fish Meal (FM) replacement in the diet of Malaysian mahseer (Tor tambroides). The POM:FM ratios tested were 0:100, 25:75, 50:50, 75:25 and 100:0. One hundred and fifty mahseer fingerlings (3.0±0.05 g) were equally and randomly stocked into 15 65 L aquaria. The diets were randomly assigned to the aquaria in triplicates groups. The feeding trial was conducted for 96 days. No significant differences (p>0.05) were observed among the survival rate of fish while it was above 90% in all the treatments. Weight gain and specific growth rate significantly increased when 50-100% of dietary fishmeal was substituted with POM. Whole body composition of Malaysian mahseer was not significantly influenced by the experimental diets. This study showed that fishmeal in the diet of mahseer can be replaced by POM up to 100% ratio without any adverse effect on survival, growth performance and body composition.